Metallaphotoredox-Catalyzed Cross-Electrophile C(sp)(3)─C(sp)(3) Coupling of Aliphatic Bromides - Smith, Russell T. (J Am Chem Soc, 2018)
A strategy for the installation of small alkyl fragments onto pharmaceutically relevant aliphatic structures has been established via metallaphotoredox catalysis. Herein, we report that tris(trimethylsilyl)silanol can be employed as an effective halogen abstraction reagent that, in combination with photoredox and nickel catalysis, allows a generic approach to C(sp)(3)─C(sp)(3) cross-electrophile coupling. In this study, we demonstrate that a variety of aliphatic drug-like groups can be successfully coupled with a number of commercially available small alkyl electrophiles, including methyl tosylate and strained cyclic alkyl bromides. Moreover, the union of two secondary aliphatic carbon centers, a long-standing challenge for organic molecule construction, has been accomplished with a wide array of structural formats. Last, this technology can be selectively merged with C(sp)(2)─C(sp)(3) aryl–alkyl couplings to build drug-like systems in a highly modular fashion.